The psychiatric sequelae of the COVID‐19 pandemic in adolescents, adults, and health care workers. Issue 2 (28th December 2020) - Murata, Stephen; Rezeppa, Taylor; Thoma, Brian; Marengo, Laura; Krancevich, Katie; Chiyka, Elizabeth; Hayes, Benjamin; Goodfriend, Eli; Deal, Meredith; Zhong, Yongqi; Brummit, Bradley; Coury, Tiffany; et al.
Abstract: Background: The COVID‐19 pandemic is the most serious global public health crisis since the 1918 influenza pandemic. This study is the first to assess its mental health impact across the lifespan in the United States in adolescents, adults, and health care workers. Methods: We recruited 4909 participants through an online survey advertising on Facebook and Instagram to assess exposure to COVID‐19 and psychiatric symptoms from April 27 to July 13. We also recruited through the University of Pittsburgh, University of Pittsburgh Medical Center, and other health care systems around Pittsburgh. The primary outcomes were clinically significant depression, anxiety, and posttraumatic stress disorder (PTSD) symptoms, suicidal ideation or behavior, and grief reactions since COVID‐19. Results: Adolescents were significantly more likely to report moderate to severe symptoms of depression (55% vs. 29%; χ 2 = 122, df = 1; p < .001), anxiety (48% vs. 29%; χ 2 = 73; df = 1; p < .001), PTSD (45% vs. 33%; χ 2 = 12; df = 1; p < .001), suicidal ideation or behavior (38% vs. 16%; χ 2 = 117; df = 1; p < .001), and sleep problems (69% vs. 57%; χ 2 = 26; df = 1; p < .001) compared to adults. The rates of intense grief reactions among those who lost someone to COVID‐19 was 55%. Loneliness was the most common predictor across outcomes and higher number of hours spent on social media and exposure to media about COVID‐19 predicted depression symptoms and suicidal ideation or behavior in adolescents. Conclusions: The COVID‐19 pandemic is associated with increased rates of clinically significant psychiatric symptoms. Loneliness could put individuals at increased risk for the onset of psychiatric disorders.